Extensive Plexiform Neurofibroma Presenting as Clitoromegaly in Neurofibromatosis Type 1 - Özlem Nalbantoğlu; Gülçin Arslan; Beyhan Özkaya; Sinan Genç; Behzat Özkan (Galenos Publishing House, 2021)
Neurofibromatosis type 1 (NF1) is an autosomal-dominant disorder with multisystem involvement. Genitourinary involvement of neurofibromatosis type 1 is rare condition and involvement of plexiform neurofibroma can cause painful clitoromegaly. A 9-year-old girl with neurofibromatosis type-1 referred with clitoromegaly to our endocrinology clinic. Pelvic magnetic resonance imaging (T2W images) showed that plexiform neurofibroma was found on the pelvic floor and peripubic region, which was 8x7x13 cm in size, extending to the external genital region and progressing to subcutaneous soft tissue. Cranial and lumbosacral magnetic resonance imaging revealed two neurofibromas in the cerebellar region and the basal ganglia. We emphasize it should be kept in mind that suspicious genitalia may develop due to infiltration of space occupying formations such as neurofibromas.